KOLABORASI ETIS GURU DAN MASYARAKAT DI ERA DIGITAL: ANALISIS STRATEGI DAN TANTANGAN PENDIDIKAN - Rizqiyana, Naila; Awaliyah, Suci; Dwi Rizqi, Mufid; Muhlisin, Muhlisin; Mafaakhir, Abul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the digital era characterized by openness of information and the complexity of social interactions, it is crucial for teachers to build ethical collaborations with the community. This study focuses on examining the methods teachers use to build ethically based collaborations and identifying various issues. The objective of the present research is to elucidate a range of methodologies for ethical collaboration among educators, as well as the obstacles they encounter during the execution of these strategies. The employed methodology constitutes a qualitative literature review approach, which encompasses the accumulation, examination, and integration of diverse scholarly resources, such as academic journals, monographs, and pertinent research publications.The results indicate that several strategies that teachers can implement include using digital technology wisely, communicating honestly, strengthening professional moral values, and actively participating in the classroom community. The lack of digital literacy among the community, the possibility of misinformation, differences in values, and limited digital skills among teachers are some of the challenges faced. The results indicate that ethical collaboration between teachers and the community requires a balance between affirming ethical values ​​and utilizing technology to create a good and sustainable relationship.